Respuesta :

Answer:

the order is

2,4,1,3

(the 1st answer is the 2nd option)

Answer:

1. (a² - b)/(a³b²)= 1/ab² - 1/a²b

2. (b - a)/a³b³ = 1/a³b² - 1/a²b³

3. (2 - ab²)/(a²b³) = 2/a²b³ - 1/ab

4. (2 - a)/a³b³ = 2/a³b³ - 1/a²b³

Step-by-step explanation:

To do this we'll break down fraction to least term through division.

The solution is as follows

1. (a² - b)/(a³b²)

Splitting the fraction;

a²/a³b² - b/a³b²

= 1/ab² - 1/a²b

2. (b - a)/a³b³

Splitting the fraction.

b/a³b³ - a/a³b³

1/a³b² - 1/a²b³

3. (2 - ab²)/(a²b³)

Splitting the fraction.

2/a²b³ - ab²/a²b³

2/a²b³ - 1/ab

4. (2 - a)/a³b³

Splitting the fraction

2/a³b³ - a/a³b³

2/a³b³ - 1/a²b³